Evaluating Student Engagement Through Student-Centered Learning Approaches In A Sports Marketing Course Among Undergraduate Students - Muhammad Faizal Kutip (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
Student-centered learning is widely recognized as an effective approach for enhancing student engagement and academic performance in higher education. This study aims to evaluate the relationship between student-centered learning constructs, namely teaching methods, assessment, and lecturer roles, with student performance among Sports Management students taking the Sports Marketing course at Universiti Teknologi MARA (UiTM). A quantitative research design was employed using purposive sampling involving 70 respondents. Data were collected through an adapted questionnaire consisting of 18 items, with high internal reliability recorded at Cronbach’s alpha of 0.949. The data were analysed using Pearson correlation and multiple regression analysis through SPSS version 29. The results showed that all three constructs had a significant positive relationship with student performance at the 0.05 level of significance, with assessment displaying the strongest correlation coefficient of 0.727. Multiple regression analysis indicated that assessment was the only significant predictor of student performance, explaining 56% of the variance. The findings suggest that assessment plays a more prominent role in influencing student performance compared to teaching methods and lecturer roles. It is therefore essential for higher education institutions to emphasize structured guidance, reflective debriefing, and continuous mentoring through effective assessment practices to promote engagement and enhance learning outcomes.